Analisis Kesulitan Siswa dalam Memahami Konsep Aljabar pada Implementasi Kurikulum Merdeka di SMP IT Az-Zahira Khatulistiwa - Anthony Matthew Hiu; Dwi Oktaviana (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze students' difficulties in understanding algebraic concepts in the implementation of the Merdeka Curriculum. This type of research uses a descriptive research method with a qualitative approach. Data collection techniques include interviews, questionnaires, and three written tests. Based on the results of interviews and questionnaires conducted by teachers with the school principal and mathematics teachers, the school has implemented the Merdeka Curriculum despite limitations in resources. The Merdeka Curriculum contributes to teachers in terms of teaching modules and freedom in creativity in learning, although training is still needed. The results of the student questionnaire indicate that the majority of students have difficulty understanding algebra, especially in identifying variables, but the majority of students feel that classroom learning is interactive and enjoyable. Most students feel helped by the example questions provided by the teacher. The written test results show that students have difficulty with the use of positive and negative signs, coefficients, constants, algebraic operations, and determining variable values. This indicates that the majority of students have not yet achieved mastery of the algebra material. It can be concluded that the implementation of the independent curriculum at SMP IT Az-Zahira Khatulistiwa supports teachers in the algebra learning process through the use of teaching modules, but students still struggle to understand algebraic concepts due to the limited use of educational media, which is constrained by the school's facilities.